Appifiering till allas lycka? Om danska ordboksappar med särskilt fokus på DDO - Holmer, Louise; Sköldberg, Emma (LexicoNordica, 2016)
In recent years, most dictionary publishers have developed dictionary apps. However, in comparison with the comprehensive scientific study of printed and web-based dictionaries, conducted research on this kind of lexicographical resource is so far limited. This article discusses four monolingual dictionary apps developed by the Society for Danish Language and Literature. The focus is on the contemporary dictionary The Danish Dictionary. Different search functions are discussed, as well as how data is presented. The article also deals with what kinds of dictionaries are best suited for the app format. A key issue is whether this format really does render all dictionaries justice, and if app development is always advisable from a user’s perspective.